PERANAN LITERASI MEMBACA DALAM MENGEMBANGKAN SIKAP MANDIRI BELAJAR SISWA SEKOLAH DASAR - Wiliwirman, Wiliwirman; Haifaturrahmah, Haifaturrahmah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This research is motivated by the crucial role of reading literacy as a foundation for independent learning in the information age. However, there is a gap between the ideal potential for literacy and the low reading ability and independent learning attitudes of elementary school students in Indonesia, as reflected in the PISA results. This research focuses on an in-depth analysis of the role of reading literacy in developing independent learning attitudes in elementary school students through a synthesis of previous research. This study used the Systematic Literature Review (SLR) method with a qualitative approach. A systematic literature search was conducted in the Google Scholar, ERIC, ResearchGate, and DOAJ databases (2020-2025), followed by article selection based on inclusion and exclusion criteria. The analysis was conducted through the stages of identification, screening, eligibility, and analysis using content analysis techniques. The synthesis results indicate that reading literacy significantly fosters independent learning by increasing students' intrinsic motivation, active engagement in learning, and self-reflection. Key findings confirm that this positive relationship is strongly influenced by the role of teachers as facilitators, a literacy-rich learning environment, and active support from parents and schools. It was concluded that strengthening reading literacy is an effective strategy for developing independent learners in elementary schools. ABSTRAKPenelitian ini dilatarbelakangi oleh peran krusial literasi membaca sebagai fondasi kemandirian belajar di era informasi, namun terdapat kesenjangan antara potensi ideal literasi dengan rendahnya kemampuan membaca dan sikap mandiri belajar siswa sekolah dasar di Indonesia, sebagaimana tercermin dalam hasil PISA. Fokus penelitian ini adalah menganalisis secara mendalam peranan literasi membaca dalam mengembangkan sikap mandiri belajar siswa sekolah dasar melalui sintesis penelitian terdahulu. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan pendekatan kualitatif. Pencarian literatur sistematis dilakukan pada database Google Scholar, ERIC, ResearchGate, dan DOAJ (rentang 2020-2025), diikuti seleksi artikel berdasarkan kriteria inklusi dan eksklusi. Analisis dilakukan melalui tahapan identification, screening, eligibility, dan analysis dengan teknik content analysis. Hasil sintesis menunjukkan bahwa literasi membaca secara signifikan menumbuhkan kemandirian belajar dengan meningkatkan motivasi intrinsik, keterlibatan aktif dalam pembelajaran, dan kemampuan refleksi diri siswa. Temuan utama menegaskan bahwa hubungan positif ini sangat dipengaruhi oleh peran guru sebagai fasilitator, lingkungan belajar yang kaya literasi, serta dukungan aktif dari orang tua dan sekolah. Disimpulkan bahwa penguatan literasi membaca merupakan strategi efektif untuk membentuk pembelajar mandiri di sekolah dasar.